The Effect of Product Innovation and Market Orientation on Competitive Advantage and Company Performance in the Small and Medium Furniture Industry in Pekanbaru City - Salamah, Ummi; Daulay, Iwan Nauli; Asrilsyak, Sharnuke (Program Pascasarjana, Universitas Riau, 2024)
The purpose of this research is to knowThe Effect of Product Innovation and Market Orientation on Competitive Advantage and Company Performance in the Small and Medium Furniture Industry in the city of Pekanbaru. In this study consists of four variables. Those variables areProduct Innovation (X1) Market Orientation (X2) on Competitive Advantage (Y1) and Company Performance (Y2). The data analysis method uses the Quantitative Descriptive method with the Path Analysis tool, with the help of using a statistical application, namely SPSS version 23. The results show that: 1) Product innovation has a significant effect on competitive advantage. 2) Product innovation has a significant effect on company performance. 3) Market orientation has a significant effect on competitive advantage. 4) Market orientation has a significant effect on company performance. 5)Competitive advantage has a significant effect on company performance. 6) Product innovation has a significant effect on company performance through competitive advantage. 7) Market orientation has a significant effect on company performance through competitive advantage.